Easy-to-Fabricate High-Gain Linearly Polarized Antenna With Tunable Beam Pattern - Anil Kumar Yerrola; Maifuz Ali; Ravi Kumar Arya; Lakhindar Murmu; Ashwani Kumar (IEEE Open Journal of Antennas and Propagation)
This paper presents an easy-to-fabricate, high-gain, linearly polarized antenna using a circular ground plane. The ground plane is made of a dielectric substrate sandwiched by two conductive sheets placed on the open end of a standard rectangular open-ended waveguide (OEWG). By modifying the aperture of OEWG, the gain of the radiating system is enhanced. Two methods are employed for such modifications, both of which deal with creating slots on the radiating front side of the conductive sheet to expose the dielectric substrate of the ground plane. In the first method, slots are introduced based on the even Fresnel zones, and their widths are optimized sequentially. This method increases the gain of the standard WR-90 waveguide from 6.86 dBi to 14.77 dBi. In the second method, surface current distributions are analyzed, and slots are introduced on the minimal surface current zones, which increases the gain to 16.59 dBi. The gain bandwidth product and 3 dB gain bandwidth are compared with the measured results. Measured results show good agreement with the Ansys HFSS simulated results. Next, an elliptical ground plane consisting of a dielectric substrate sandwiched between two conducting layers and elliptical slots is used to generate symmetric beam patterns of the E- and H-plane on the front side of the TE10 waveguide (WR-28). The modified Fresnel zone theory helped modify the circular ground plane to an elliptical ground plane and identify the elliptical slots. The introduced elliptical slots that helped generate the symmetrical beam pattern in the range of $-45^{° }≤ θ ≤ 45^{° }$ are introduced based on the modified Fresnel zone equation. Lastly, a modification of the edge along the E-plane helped generate a symmetrical beam pattern in the range of $-90^{° }≤ θ ≤ 90^{° }$ .